Pengelolaan Zakat, Infaq, dan Sedekah di LAZISNU Babadan - Ponorogo Perspektif Ekonomi M. Umer Chapra - Fudaili, Muhammad (Nidhomiya: Research Journal of Islamic Philanthropy and Disaster, 2024)
This article analyzes the management of zakat, infaq, and alms from an economic perspective explained by M. Umer Chapra. Chapra is a leading Islamic economist who has made significant contributions to understanding the principles of Islamic economics and their implementation in Muslim financial practices. This study explores the concept of managing zakat, infaq, and alms as economic instruments that can potentially strengthen the Muslim economy. The main focus of this journal is to analyze the principles proposed by M. Umer Chapra in managing these religious funds, as well as their impact on the economic empowerment of Muslim communities. Through a careful literature review, this research outlines Chapra's views on how zakat, infaq, and alms can be integrated into the Islamic economic system to achieve the goals of sustainable and inclusive economic development. This journal also discusses best practices in managing zakat, infaq, and alms following the economic principles recommended by Chapra. It is hoped that the results of this research will provide deeper insight into the management of zakat, infaq, and alms from an economic perspective, as well as positively contribute to developing a more effective and efficient model for managing religious funds. Policy implications and suggestions for further development are also discussed in this journal, providing a basis for stakeholders, academics, and practitioners to improve the implementation of Islamic economic principles in the management of zakat, infaq, and alms. Artikel ini menganalisis pengelolaan zakat, infaq, dan sedekah dari perspektif ekonomi yang dijelaskan oleh M. Umer Chapra. Chapra merupakan seorang ekonom Islam terkemuka yang telah memberikan kontribusi signifikan dalam memahami prinsip-prinsip ekonomi Islam dan implementasinya dalam praktik keuangan umat Muslim. Studi ini mengeksplorasi konsep pengelolaan zakat, infaq, dan sedekah sebagai instrumen ekonomi yang memiliki potensi untuk memperkuat perekonomian umat Muslim. Fokus utama artikel ini adalah menganalisis prinsip-prinsip yang diusulkan oleh M. Umer Chapra dalam mengelola dana keagamaan ini, serta dampaknya terhadap pemberdayaan ekonomi komunitas Muslim. Melalui tinjauan literatur yang cermat, penelitian ini menguraikan pandangan Chapra tentang bagaimana zakat, infaq, dan sedekah dapat diintegrasikan dalam sistem ekonomi Islam untuk mencapai tujuan pembangunan ekonomi yang berkelanjutan dan inklusif. Artikel ini juga membahas praktik-praktik terbaik dalam pengelolaan zakat, infaq, dan sedekah yang sesuai dengan prinsip-prinsip ekonomi yang dianjurkan oleh Chapra. Hasil penelitian ini diharapkan dapat memberikan wawasan yang lebih mendalam tentang pengelolaan zakat, infaq, dan sedekah dari perspektif ekonomi, serta memberikan kontribusi positif terhadap pengembangan model pengelolaan dana keagamaan yang lebih efektif dan efisien. Implikasi kebijakan dan saran-saran untuk pengembangan lebih lanjut juga dibahas dalam artikel ini, memberikan landasan bagi pemangku kepentingan, akademisi, dan praktisi untuk meningkatkan implementasi prinsip-prinsip ekonomi Islam dalam pengelolaan zakat, infaq, dan sedekah.